7th APEEN Conference / Energy Economics International Conference - Meireles, M.; Madaleno, M.; Alves, M. R. (7th APEEN Conference / Energy Economics International Conference, 2023)
Economic activities have arisen several environmental problems. Consequently, their energy transition and the switch to circular economy practices are fundamental to reach environmental sustainability. Therefore, eco-innovation plays a crucial role in promoting the conversion from dirty to clean energy and from a linear to a circular economy. We provide a deeper knowledge of European companies' adoption of environmental and energy innovations using the most recent CIS (Community Innovation Survey) data, that of 2020. Additionally, we attempt to compare eco-innovation adoption with the 2014 CIS results, considering different firm-size groups. Globally, fewer companies answered the CIS 2020 survey; in 2014 companies were more focused on product eco-innovation, while in 2020 attention turned more to business process eco-innovations; moreover, size matters concerning factors related to climate change. Policymakers should be aware of the size and compliance of the energy transition, as important drivers when forcing firms to introduce policies regarding environmental benefits.